A child with a special future! How the understanding of the noun גבר enriches the translation - Roelie van der Spuy (In die Skriflig, 2024)
Gird your loins and answer God like the ‘hero of faith’ (גבר [geber]) you claim to be! According to some scholars in both divine speeches, God challenges Job to get ready and reply, according to Job’s claim of being a ‘hero of faith’ (גבר [geber]). If it is true that Job is a ‘hero of faith’ (גבר [geber]), then a whole new dimension can be brought to light in the translation of the Hebrew lexeme geber in Job 3:3. This would have profound implications for how to translate Job 3:3 where Job is referring to himself, cursing the night when it was announced that a ‘hero of faith’(גבר [geber]) is conceived! This study contests the claim that this reference would be the only instance in the Bible where גבר [geber] would carry the nuanced meaning of male child, or ‘baby boy’ (NIV). If geber indeed emphasises that Job is a child with a special future, then in most translations, the carefully construed Hebrew emphasis is lost. This relates to most mainline Bible translations, as well as vernacular translations, which just follow suit, i.e. translating Job 3:3 just like previous translations have done.